Мода як гра - Даценко, Вікторія (Видавництво Львівської політехніки, 2017)
The coverage of fashion is boundless and extends to various directions of social life, culture and behavior of the person. The fashion is attractive. The fashion belongs not to the world of things, and the world of people. Game becomes a basis of designing of the sociality. Presence of value of a game at structure of fashion partly explains broad interpretation of fashion as esthetic phenomenon. Game, as well as fashion differs in heuristic, search character. She is connected with festive attitude. The fashion is one of means of self-affirmation and selfrealization.
Keywords: мода; суспільство; комунікація; гра; культура; естетика